2015
DOI: 10.1371/journal.pcbi.1004189
|View full text |Cite
|
Sign up to set email alerts
|

Distal Spike Initiation Zone Location Estimation by Morphological Simulation of Ionic Current Filtering Demonstrated in a Novel Model of an Identified Drosophila Motoneuron

Abstract: Studying ion channel currents generated distally from the recording site is difficult because of artifacts caused by poor space clamp and membrane filtering. A computational model can quantify artifact parameters for correction by simulating the currents only if their exact anatomical location is known. We propose that the same artifacts that confound current recordings can help pinpoint the source of those currents by providing a signature of the neuron’s morphology. This method can improve the recording qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 72 publications
2
33
0
Order By: Relevance
“…Database and model reconstruction approaches have been used to fit ion channel distributions on anatomical reconstructions of known neurons [3032, 33•]. A recent study showed that, to maintain functional properties along the dendritic tree of a neuron, mechanisms that tune the number of all ion channels collectively are more likely than those that tune the number of individual ion channels – this would not have been seen in single-compartment models [34•].…”
Section: Neuronal Intrinsic Excitability Occurs At Multiple Timescalesmentioning
confidence: 99%
“…Database and model reconstruction approaches have been used to fit ion channel distributions on anatomical reconstructions of known neurons [3032, 33•]. A recent study showed that, to maintain functional properties along the dendritic tree of a neuron, mechanisms that tune the number of all ion channels collectively are more likely than those that tune the number of individual ion channels – this would not have been seen in single-compartment models [34•].…”
Section: Neuronal Intrinsic Excitability Occurs At Multiple Timescalesmentioning
confidence: 99%
“…2b-g). We first considered larval motor neurons aCC and RP2 (Landgraf et al, 1997), which have functional and structural similarities to vertebrate neurons (Sánchez-Soriano et al, 2005;Nicolaï et al, 2010;Günay et al, 2015).…”
Section: Microtubule-free Twigs Are the Principal Site Of Synaptic Inputmentioning
confidence: 99%
“…As the information about the thickness of each branch will soon be available in the database, we will be able to more accurately calculate the area of the membrane and thus derive better estimates for related parameters. Adopting a multi-compartmental model will also help to improve the accuracy of the simulations (Günay et al 2015). Moreover, some neurons in the visual system conduct signals by graded potentials or by mixed graded and action potentials (Mu et al 2012;Baden et al 2013).…”
Section: Discussionmentioning
confidence: 99%